Comparative genomics analyses of Actinobacteriota identify Golgi phosphoprotein 3 (GPP34) as a widespread ancient protein family associated with sponge symbiosis - Cláudia Ferreira; Ilia Burgsdorf; Tzipora Perez; Gustavo Ramírez; Maya Lalzar; Dorothée Huchon; Laura Steindler (Microbiome)
Abstract Background Sponges harbor microbial communities that play crucial roles in host health and ecology. However, the genetic adaptations that enable these symbiotic microorganisms to thrive within the sponge environment are still being elucidated. To understand these genetic adaptations, we conducted a comparative genomics analysis on 350 genomes of Actinobacteriota, a phylum commonly associated with sponges. Results Our analysis uncovered several differences between symbiotic and free-living bacteria, including an increased abundance of genes encoding prokaryotic defense systems (PDSs) and eukaryotic-like proteins (ELPs) in symbionts. Furthermore, we identified GPP34 as a novel symbiosis-related gene family, found in two symbiotic Actinobacteriota clades, but not in their closely related free-living relatives. Analyses of a broader set of microbes showed that members of the GPP34 family are also found in sponge symbionts across 16 additional bacterial phyla. While GPP34 proteins were thought to be restricted to eukaryotes, our phylogenetic analysis shows that the GPP34 domain is found in all three domains of life, suggesting its ancient origin. We also show that the GPP34 family includes genes with two main structures: a short form that includes only the GPP34 domain and a long form that encompasses a GPP34 domain coupled with a cytochrome P450 domain, which is exclusive to sponge symbiotic bacteria. Conclusions Given previous studies showing that GPP34 is a phosphatidylinositol-4-phosphate (PI4P)-binding protein in eukaryotes and that other PI4P-binding proteins from bacterial pathogens can interfere with phagolysosome maturation, we propose that symbionts employ GPP34 to modulate phagocytosis to colonize and persist within sponge hosts. Video Abstract